Crimes against property in Tungurahua - Tamayo, Jorge (2016)
Homicide rates are the reflection of the violence generated in any society and especially in those crimes that have to do with the vandalism of private property, which causes a real and personal sense of insecurity in the province of Tungurahua. Commercial, financial, and banking activities are affected daily by crime. These are enacted in a violent form under the influence of alcohol and other controlled substances. In continuation the number of crimes which were registered in Tungurahua in the catagories of theft and petty theft, also including vandalism were seen as being the ones of the most commonly occurring during the first part of 2016. DOI: https://doi.org/10.31164/bcoyu.10.2016.612 URL: http://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/612